1965
DOI: 10.1085/jgp.48.4.617
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Erythrocyte Membrane Sulfhydryl Groups Essential for Glucose Transport

Abstract: The reactions of three organic mercurial compounds, chlormerodrin, parachloromercuribenzoate (PCMB), and parachloromercuribenzenesulfonate (PCMBS) with intact red blood cells, hemolyzed red cells, hemoglobin solutions, and hemoglobin-free ghosts have been characterized. Both PCMB and PCMBS react with only 2 to 3 sulfhydryl groups per mole of hemoglobin in solution, whereas chlormerodrin reacts with 6 to 7. In hemoglobin-free ghosts, however, all three reagents react with a similar number of sulfhydryl groups, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

1967
1967
1990
1990

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(91 citation statements)
references
References 11 publications
5
86
0
Order By: Relevance
“…Lost intracellular NAD could be quantitatively recovered in the extracellular fluid, indicating that it was not degraded, but lost due to permeability changes in the plasma membrane. same changes were observed in the presence ofpCMBS, which acts primarily with plasma membrane -SHs (44,45,52). The additive effect of HOCI and pCMBS on 06Rb efflux, aminoisobutyric acid uptake and increase in cell volume suggests that the two reagents act upon functionally similar cellular targets, presumably extracellularly accessible -SH groups.…”
Section: Hoci-induced Cell Lysismentioning
confidence: 55%
See 2 more Smart Citations
“…Lost intracellular NAD could be quantitatively recovered in the extracellular fluid, indicating that it was not degraded, but lost due to permeability changes in the plasma membrane. same changes were observed in the presence ofpCMBS, which acts primarily with plasma membrane -SHs (44,45,52). The additive effect of HOCI and pCMBS on 06Rb efflux, aminoisobutyric acid uptake and increase in cell volume suggests that the two reagents act upon functionally similar cellular targets, presumably extracellularly accessible -SH groups.…”
Section: Hoci-induced Cell Lysismentioning
confidence: 55%
“…If cells were lysed with 0.01% digitonin before the addition of HOCI, 90% inactivation of GAPDH was seen with 10 gM HOCl, indicating that the cytoplasmic location protects GAPDH from inactivation in intact cells to a considerable degree, but not completely. pCMBS similarly inactivated GAPDH (59% inactivation at 10 gM) in spite of its poor membrane permeability (44). (Table III), but may have been due to inhibition of glucose uptake rather than GAPDH inactivation.…”
Section: Hoci-induced Cell Lysismentioning
confidence: 92%
See 1 more Smart Citation
“…Such an effect may be explicable in terms of differing heat sensitivities ofthevarious enzymes, depending upon their direction towards the inside or outside of the membrane. Vansteveninck, Weed, and Rothstein (1965) have shown that only about 5% of the sulphydryl groups of the red cells are directed towards the outside of the membrane, Fig. 8 Bottom 9% of whole normal blood heated in vitro for 10 minutes at 480C.…”
Section: Discussionmentioning
confidence: 99%
“…Physiological experiments have proved that SH groups in human erythrocyte membrane are involved in many membrane functions (see review (29)); permeability of cations (31), transport of sugars (35) and water (22) and activity of membrane enzymes (such as Na-K-ATPase) (38). These functions are disturbed by chemical reagents with a degree of specificity for SH groups.…”
Section: Methodsmentioning
confidence: 99%